موقع الصين المستقبلي في النظام الدولي - حكيمـــي, توفيـــق (revue mofakir; No 12 (2015): مجلـــة المفكــر, 2018)
Throughout history, the arrival of a new great power on the world scene. From the Peloponnesian War over two thousand years ago to the rise of Germany in this century, almost every new addition to the ranks of the great powers has resulted in global instability and war. E. H. Carr correctly identified the "problem of peaceful change" as the central dilemma of international relations. In this article we will discuss the debate among scholars and policymakers about what China will do with its newfound capabilities, generally Two arguments have dominated the debate. One focuses on power and likely Chinese revisionism, and so, China will follow the path of rising power such as Germany and Japan before the second world war, The other highlights China’s growing interdependence and likely future satisfaction.ie China would increasingly enmesh itself in and support the existing rules of international society.